Managing the value gap among generations in organizations: socio-psychological approach - Sahraee, Rezvan; Abdullah, Haslinda (Human Resource Management Academic Research Society, 2017)
Over the few past decades, value gap among generations has presented new challenges for organizations. Although studies have suggested value congruence as a mechanism to bring generations closer together, this study presents evidence showing that providing an autonomy-supportive environment, where higher levels of psychological need satisfaction for autonomy, competence, and relatedness are experienced by employees, facilitates the process of internalization and embrace of others' values. Such a context would result in better communication, mutual understanding, and bridging the generation gap effectively at workplace.